Pengaruh Motivasi Kerja dan Kemampuan Kerja Terhadap Kinerja Karyawan Pada PT Pegadaian - Hasnah, Muh. Ikbal; Yaqin, Muhammad Ismail; Mallibureng, Evi; Rayhan, Andi Muhammad; Hasrialdi, Hasrialdi; Dinsar, Arfandy (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This reseacch aims to determine whether motivation and work ability have a significant partial and simultaneous effect on employee performance at PT Pegadaian Parepare City branch. This thesis uses a descriptive quantitative approach, with data collection methods through observation and questionnaires. Based on research, the results and conclusions obtained are that motivation variables influence employee performance. Based on the results of the t test, the calculated t value was 2.323 with a significant value of 0.032<0.05. The work ability variable influences employee performance. Based on the results of the t test, the calculated t value was 3.326 with a significant value of 0.004<0.05. And motivation and work ability variables influence employee performance in the study of PT Pegadaian Parepare City branch employees. Based on the results of the f test, the calculated f value was 48.021 with a significant value of 0.000<0.00.